Born-digital field survey data: using a KoBoToolbox workflow in the West Area of Samos Archaeological Project - Loy , Michael; Katevaini , Alexandra; Vasileiou , Anastasia (Journal of Greek Archaeology, 2024)
Since 2021, the west part of Samos, located between Mt Karvounis and Mt Kerkis, has been under archaeological investigation by the British School at Athens, as part of the West Area of Samos Archaeological Project (WASAP).The project’s sizeable study area, covering two basins in the environs of the contemporary settlements of Karlovasi (in the north) and Marathokampos (in the south), has variously featured in ancient and Early-Modern texts and in the occasional reports from the Hellenic Ministry of Culture; but the work of WASAP represents the first systematic, multi-period and broad-coverage landscape study of the area. A core research goal of the project, therefore, is to conduct reconnaissance survey, to map as widely as possible loci of archaeological interest across this vast plain.